2009
DOI: 10.1890/08-1409.1
|View full text |Cite
|
Sign up to set email alerts
|

The coupling of biodiversity and productivity in phytoplankton communities: consequences for biomass stoichiometry

Abstract: Abstract. There is widespread concern that loss of biodiversity can influence important ecosystem services. A positive relationship between diversity and productivity has been observed in investigations of terrestrial and aquatic plant communities. However, an increase in primary production (carbon assimilation) does not necessarily result in higher nutrient uptake by primary producers. There is a loose coupling between carbon assimilation and nutrient uptake in autotrophs, and their biomass carbon-to-nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 36 publications
8
56
1
1
Order By: Relevance
“…This linkage is well documented in terrestrial systems (3)(4)(5)(6)(7) and is increasingly being established for marine systems (8)(9)(10)(11). Marine phytoplankton generate roughly half of global primary production (12)(13)(14) and play a critical role in oceanic ecosystem structure and function.…”
mentioning
confidence: 96%
“…This linkage is well documented in terrestrial systems (3)(4)(5)(6)(7) and is increasingly being established for marine systems (8)(9)(10)(11). Marine phytoplankton generate roughly half of global primary production (12)(13)(14) and play a critical role in oceanic ecosystem structure and function.…”
mentioning
confidence: 96%
“…In addition, we analyzed seston C:P ratios from natural phyto plankton communities as a function of the contribution of potentially mixotrophic species to the total phytoplankton community. We utilized data from 2 lake surveys that were carried out during summer stratification in 2004 (Striebel et al 2009a(Striebel et al , 2009b and 2012 (Horváth et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Combination of multiple community ecology theories would certainly improve our understanding of community stoichiometry, since competition theory alone does not explain the high biodiversity found in, for example, phytoplankton communities (Passarge et al, 2006). Species diversity is a factor that has received special interest recently, both as a factor affecting (Striebel et al, 2009;Abbas et al, 2013) and being affected by stoichiometry (Evans-White et al, 2009;Lewandowska et al, 2016). The study by Guiz et al (2016) is unique in its attempts at causally explaining both the mean and variation in stoichiometry within local communities and suggests an intriguing convergence in the mean and variance of C:N ratios between plant communities established on different soil fertilities.…”
Section: Communitymentioning
confidence: 99%
“…This example points to the importance of considering the potential feedbacks between the chemical environment and recycling ( Table 2). Research in biodiversity-ecosystem functioning relationships has otherwise shown that species diversity affects elemental rates within ecosystems (Hooper et al, 2005), as well as biomass production and stoichiometry of primary producers (Striebel et al, 2009). However, interactive effects of stoichiometry and biodiversity on recycling rates are still poorly understood and in need of further development (Hillebrand et al, 2014).…”
Section: Recycling Ratesmentioning
confidence: 99%